Factors Affecting the Complication Rate of Septoplasty: Analysis of 1,506 Consecutive Cases of Single Surgeon - Shin, Chol Ho; Jang, Yong Ju (Facial Plastic Surgery, 2023)
Based on the analysis of a single surgeon's consecutive cases, we present the incidence of septoplasty complications and factors that contribute to the increased risk of complications. We retrospectively reviewed the medical records from 1,506 patients diagnosed with deviated nasal septum who underwent septoplasty by a single surgeon from January 2003 until May 2020. The incidence of different complications was investigated. Predisposing factors for specific complications were examined with univariate analysis. The average age of patients was 35 (11–76) years. Out of 1,506 patients, 1,252 were male, and 254 were female. The most frequent complication was insufficient correction (78 cases, 5.2%), and revision septoplasty was performed in 21 cases. We also reported 59 (3.9%), 55 (3.7%), 33 (2.2%), 20 (1.3%), and 18 (1.2%) cases of olfactory dysfunction, hematoma, synechia, abscess, and septal mucosal defect, respectively. Additionally, there were nine (0.6%), six (0.4%), five (0.3%), four (0.3%), and four (0.3%) cases of septal perforation, postoperative bleeding, saddle nose, chondritis, empty nose syndrome, respectively. The proportion of insufficient correction was higher in revision cases than in primary cases. Hematoma formation, abscess formation, and septal mucosal defect occurred more frequently in the bilateral flap elevation group. Olfactory dysfunction was significantly more frequent when the bony batten was inserted, while hematoma, abscess formation, and septal mucosal defect were more frequent when the cartilage batten was used. Septoplasty was associated with the risk of several complications, while complication rates were influenced by choice of surgical techniques and approaches.
Keywords: septoplasty; complications; bilateral flap elevation; batten graft